2021
DOI: 10.1136/jech-2020-216220
|View full text |Cite
|
Sign up to set email alerts
|

Deaths from ‘diseases of despair’ in Britain: comparing suicide, alcohol-related and drug-related mortality for birth cohorts in Scotland, England and Wales, and selected cities

Abstract: BackgroundThe contribution of increasing numbers of deaths from suicide, alcohol-related and drug-related causes to changes in overall mortality rates has been highlighted in various countries. In Scotland, particular vulnerable cohorts have been shown to be most at risk; however, it is unclear to what extent this applies elsewhere in Britain. The aim here was to compare mortality rates for different birth cohorts between Scotland and England and Wales (E&W), including key cities.MethodsMortality and popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Moreover, while IHD’s contribution to GGLE has declined across the UK, the role of drug-related deaths rose. Drug-related deaths belong to the “deaths of despair” [ 46 ], which are attributable to socio-economic conditions rather than healthcare policies and have been increasing also in the UK [ 47 ]. The slowdown in LE growth may be attributed to other than winter-related mortality in the UK (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while IHD’s contribution to GGLE has declined across the UK, the role of drug-related deaths rose. Drug-related deaths belong to the “deaths of despair” [ 46 ], which are attributable to socio-economic conditions rather than healthcare policies and have been increasing also in the UK [ 47 ]. The slowdown in LE growth may be attributed to other than winter-related mortality in the UK (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings suggest that the suicide mortality rate trend in the US is not necessarily an indicator of an upcoming global trend and may in fact be atypical, as Case and Deaton [ 3 ] and others [ 24 ] have postulated with respect to the so-called deaths of despair in general. Even though a similar trend could be occurring elsewhere (for example, see [ 7 ]), it appears to be restricted to certain countries. Generally speaking, we found that in the US, gender-specific suicide mortality rates are increasing, while in Lithuania the rates are decreasing.…”
Section: Discussionmentioning
confidence: 58%
“…Countries in the UK have also experienced recent rises in middle-aged mortality,[ 6 ] for which the increasing number of deaths by suicide among this age group has been identified as a contributory factor. [ 7 ] However, it is unclear whether this is also happening in other parts of the world including countries of the European Union (EU). To the best of our knowledge, there has not been a study done to date using advanced statistical methods to compare the suicide mortality rate trend in the US with any country in the EU.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide is a complicated human affliction at the very core of deaths by despair. We continue to see increases in these premature deaths (Shanahan et al, 2019;Walsh et al, 2021) amid long-standing recommendations for more routine suicide risk assessments (SRA; Hawton & van Heeringen, 2009). Regrettably, with low-validity SRAs, researchers may naïvely present unreliable findings and clinical decisions may be poorly guided.…”
Section: Adultsmentioning
confidence: 99%